Thermophysical properties of selected cash crops grown in Ghana - Bart-Plange, Ato (Prof) (2015)
A Thesis submitted to the Department of Agricultural Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food and Postharvest Engineering.